2022
DOI: 10.3389/fpubh.2022.895510
|View full text |Cite
|
Sign up to set email alerts
|

Grit and Life Satisfaction Among College Students During the Recurrent Outbreak of COVID-19 in China: The Mediating Role of Depression and the Moderating Role of Stressful Life Events

Abstract: The global recurrent outbreak of COVID-19 has brought immense psychological distress to those affected. We conducted this study to explore the relationship among grit, stressful life events, depression, and life satisfaction in college students during the recurrent outbreak of COVID-19. According to the properties of the bias-corrected bootstrap method, we surveyed 888 college students, with an average age of 20.84 (SD = 1.57) years. Participants completed questionnaires regarding grit, depression, stressful l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…For example, research based on the elderly shows that happiness of older adult is highly correlated with their mental health ( Won et al, 2021 ). Children who grow up in families with higher levels of parental support and better atmosphere have higher levels of happiness, making them mentally healthier ( Lee et al, 2006 ; Morris et al, 2007 ) In addition, studies on college students reveal that stressful life experiences reduce their subjective well-being, which leads to a higher rate of mental illness ( Liu et al, 2022 ). However, data sources, explanatory variables, dependent variables, and statistical methods used in different researches vary greatly, so their analytical results are not comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research based on the elderly shows that happiness of older adult is highly correlated with their mental health ( Won et al, 2021 ). Children who grow up in families with higher levels of parental support and better atmosphere have higher levels of happiness, making them mentally healthier ( Lee et al, 2006 ; Morris et al, 2007 ) In addition, studies on college students reveal that stressful life experiences reduce their subjective well-being, which leads to a higher rate of mental illness ( Liu et al, 2022 ). However, data sources, explanatory variables, dependent variables, and statistical methods used in different researches vary greatly, so their analytical results are not comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, happiness is one of the important indicators to measure the mental welfare of children. Besides, studies on college students reveal that stressful life experiences reduce their subjective well-being, which may lead to a higher rate of mental illness and even suicidal tendencies ( Liu et al, 2022 ). In addition, previous studies have shown that there are variations in mental health status across groups with different demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Grit possesses extreme steadfastness and determination to sustain the same amount of pleasure and passion every day for an extended time ( Stoffel and Cain, 2018 ). The higher the level of grit, the easier it is for an individual to see difficulties and stress in life as an ultimate part of their struggle to achieve long-term goals, and this motivation makes them less likely to be depressed ( Liu et al, 2022 ). Grittier students outperform their peers in academics, do not give up after minor setbacks, maintain a healthy balance of curricular and extracurricular activities, and are better able to overcome mental health challenges during the COVID-19 pandemic ( Loftus et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(37) Sin embargo, una menor satisfacción con la vida emerge como un predictor de trastornos mentales. (38) De este modo, la mejora de la satisfacción con la vida se revela como un elemento fundamental para que los estudiantes universitarios no solo se adapten de manera efectiva al entorno académico, sino que también experimenten un crecimiento saludable en su trayectoria educativa.…”
Section: Satisfacción Con La Vidaunclassified